PANDANGAN MASYARAKAT INDONESIA TERHADAP CHILDFREE OLEH KAUM LIBERALIS - Fithrotunna Muqowwamatul Millah (UNIVERSITAS SEBELAS MARET (UNS), 2024)
The world is having globalization, especially in culture. Childfree is one of the many cultures as well as the ideology of western society which has been globalization into the layers of Indonesian society. This has received public scrutiny because it is considered to be very incompatible with the idealistic Indonesian family culture. To find out the public's view of childfree by liberalism, the authors use a comparative method by making comparisons of the variables tested. The results of the research show that people who are against childfree are people who have high religious values and have a strong spirit of upheld culture. Meanwhile, the majority of people who are pro with western ideology are the millennial generation who have precipitated citizenship rights but have not acculturated a new culture. They are individuals who really care about their future careers. Childfree is a western culture that enters Indonesia and undermines society's construction of the ideal family. However, if we review it again, the western ideology, which is considered too liberal by the people, contains the value of rights as citizens which cannot be interfered with by other people in statutory regulations.